EB virus-positive tumors are inhibited by rBCG expressing hGM-CSF and LMP2A - Yingchun Yan; Qing-Jie Xue; Ang Liu; Hui Wang; Honghua Zhang; Shuang Wang; Longyu Zhao; Yunqing Li; Xiuzhen Li; Yuanyuan Yang; Ting Chen; Shigen Li (Human Vaccines & Immunotherapeutics, 2020)
For the development of safe and effective EBV (Epstein-Barr virus) vaccines, the Ag85A signal peptide from M. tuberculosis H37Rv was used to construct a recombinant secretory BCG (Bacillus Chalmette-Guérin) plasmid. The Ag85A gene, fused to the EBV LMP2A (latent membrane protein) and hGM-CSF (human granulocyte/macrophage colony-stimulating factor) genes, was inserted into the pMV261 vector (secretory BCG plasmid). The expression levels of the hGM-CSF and LMP2A proteins in rBCG (recombinant BCG) were measured by Western blot analysis. Humoral immunity, cellular immunity, and antitumor effects were determined by a series of experiments. The recombinant pMVGCA plasmid effectively expressed GCA (hGM-CSF and LMP2A fusion protein) in BCG after transformation, and the rBCG proteins were recognized by antibodies against hGM-CSF and LMP2A. Six weeks after immunization, the maximum dose of rBCG resulted in antibody titers of 1:19,800 (hGM-CSF antibody) and 1:21,800 (LMP2A antibody). When the effector:target ratio was 40:1, specific lysis was maximal and approximately two times stronger than that in mice immunized with the control. Tumorigenicity was lower in the rBCG treatment group, with a tumor inhibition rate of 0.81 ± 0.09 compared with the control groups. EB virus-positive tumors are inhibited by rBCG expressing an hGM-CSF and LMP2A fusion protein.